Enterprise fragmentation in the Czech transformation: Emerging patterns of dependence and independence - Ed Clark (Journal for East European Management Studies, 2001)
This paper examines the process whereby the former state-owned enterprises in the Czech Republic have been fragmented and repackaged into privatised and private firms. By studying the process in two local communities, this research enriches the statistical picture compiled by economists working within a neoclassical paradigm. The findings highlight the diversity of fragmentation patterns and the role played by community, enterprise and management factors. They throw doubts upon the claim that fragmentation has in any simple way created new, independent entrepreneurial firms. The processes of fragmentation do however point to the emergence of distinctive forms of local economic organisation. – – In dieser Arbeit wird untersucht, auf welche Art und Weise alte Staatsunternehmen in der tschechischen Republik geteilt und in privatisierte und private Unternehmen umgewandelt wurden. Durch die Studie in zwei Gemeinden wird das statistische Gesamtbild bereichert, das von Ökonomen, die nach dem neo-klassischen Paradigma arbeiten, aufgebaut wurde. Die Untersuchungsergebnisse heben die Unterschiedlichkeit der Fragmentierungsmuster ebenso hervor, wie die Rollen, die von der Kommune, vom Unternehmen und von verschiedenen Managementfaktoren gespielt werden. Nach dieser Studie darf an der Behauptung gezweifelt werden, dass Fragmentierung auf irgedeine einfache Art und Weise neue, unabhängige Unternehmen geschaffen hat. Die Fragmentierungsprozesse bringen jedoch verschiedene Formen lokaler ökonomischer Organisation ans Licht.
Keywords: 650